Universal correlation for falling film evaporation on a horizontal plain tube. (February 2023) - Lin, Hao-Yu; M, Muneeshwaran; Yang, Cheng-Min; Nawaz, Kashif; Wang, Chi-Chuan
Highlights: A new equation for falling film evaporation on a horizontal plain tube is proposed. The new correlation includes nucleate boiling, film evaporation, and dry-out. The proposed correlation covers a wider range of operating conditions. 8 fluids (R134a, R245fa, R1234ze(E), R123, R32, R410A, R290, and R600a) is covered. A novel expression is developed for the enhancement factor and suppression factor. Abstract: Falling film evaporators are widely used in many industrial sectors, such as desalination, refrigeration & air-conditioning, and chemical processes. The heat transfer correlations suitable for wider operating conditions and various refrigerants are useful for designing falling film evaporators. Although many researchers developed the correlation for their own experimental data, there is a limited universal correlation for falling film evaporators. In addition, the dry-out effects were not considered in the available universal correlations. Therefore, this study proposes a new correlation for falling film evaporation on a single horizontal plain tube, which includes nucleate boiling, film evaporation, and dry-out effects. The proposed correlation covers a wider range of operating conditions (Heat flux is of 2.5–168  k W m − 2, and film Reynolds number is up to 3500), various refrigerants (R134a, R245fa, R1234ze(E), R123, R32, R410A, R290, and R600a), and the large number of experimental data (1101 data in total). The proposed correlation is validated against the available standard correlation with regard to mean absolute deviation (MAD) and R 2 values. The MAD of the new correlation is about 10%, respectively, which is the lowest among other correlations. Similarly, the R 2 showed a value of 0.92, which is the highest compared to the existing correlations. A simplified correlation is also proposed.